Relihiyon at Relasyong Panlabas: Gawaing Pangmisyon ng mga Koreanong Methodist at Presbyterian sa Pilipinas (1973-2000) - Abejo, Raymund Arthur (Philippine Social Sciences Review, 2016)
This study traces the historical development of Korean Protestant missions in the Philippines, focusing on Korean Presbyterian and Methodist churches, and examines the effects of the mission activities on cross cultural relations between the Philippines and South Korea. The Philippines is one of the major destinations for Korean missionaries. From 1973 when the first Korean missionaries arrived in the Philippines and up until 2000, the Presbyterian and Methodist mission agencies operated separately and with little interdenominational cooperation. But while the Korean Methodist Church missionaries cooperated closely with the United Methodist Church of the Philippines, the Presbyterian mission agencies failed to foster closer ties with existing Philippine Protestant churches due to their weak ecumenical fervor. However, both the Presbyterian and Methodist churches were able to undertake successful independent activities because of their strong financial capacity and the zeal of Korean missionaries. Mission activities generally revolve around three major undertakings: church-planting through a Filipino Protestant church or a recruited Filipino pastor; the training of pastors and laypeople; and the establishment of kindergartens, elementary schools, and high schools. Overall, the Korean Protestant missions served as bridge of cultural interactions and linkages between the people of the two countries. Through resulting interactions, both Filipinos and Koreans were able to conceive their respective image of one another.
Keywords: cross cultural exchange, Korean missionaries, Korean Protestants, Protestant missions in the Philippines, transnational actors